EDUKASI DAN HUKUM: SOSIALISASI PENCEGAHAN KEKERASAN TERHADAP ANAK DI KECAMATAN CIOMAS - Indah Nabihatul Aulawiyah; Triyani Dewita; Nurul Ghoniyah; Mila Karmila; Iin Satriani; Anton Nasrullah; Widya Dwiyanti; Harry Qurba (Yayasan Education and Social Center, 2022)
Children are a gift from God that must be guarded and protected with love. Child Protection Act number 23 of 2002-chapter l Article l paragraphs 1 and 2: 1) a child is a person under the age of eighteen years, including children who are still in the womb, 2) child protection is all activities to guarantee and protect children. Moreover, the right to live, grow, develop, and participate optimally by human dignity and protection from violence and discrimination. However, the reality is that recently there has been much violence against children, whether physical, emotional, neglect or sexual abuse; this is due to a lack of education and laws on stopping violence against children. Usually, the perpetrators of violence against children are people who are close to the child, such as parents, teachers, adults around the child, and their peers; For this reason, students and lecturers conduct education and law on socializing the prevention of violence against children to provide ideas for residents around Ciomas District, Serang Regency so that they get enlightenment about the importance of educating children without violence because children are the forerunner of the future